2017
DOI: 10.5398/medpet.2017.40.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Pattern, Forage Yield, and Quality of Indigofera zollingeriana Influenced by Row Spacing

Abstract: Indigofera zollingeriana is one of legumes has a great potential to be used as an animal feed having high quality nutrients and is tolerant to different environmental conditions. The objective of this experiment was to study the effect of different row spacings between individual plants on growth pattern, forage yield, and quality of I. zollingeriana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
2
13
1
6
Order By: Relevance
“…higher than 20% DM (Table 1). Such high CP contents of indigofera, papaya and moringa leaves were also reported in other experiments, typically ranged from 24-28% DM (Jayanegara et al, 2016;Kumalasari et al, 2017;Syarifuddin et al, 2017). Ensiling treatment decreased CP contents of indigofera and moringa but not papaya leaves.…”
Section: Chemical Composition and Silage Qualitysupporting
confidence: 86%
See 1 more Smart Citation
“…higher than 20% DM (Table 1). Such high CP contents of indigofera, papaya and moringa leaves were also reported in other experiments, typically ranged from 24-28% DM (Jayanegara et al, 2016;Kumalasari et al, 2017;Syarifuddin et al, 2017). Ensiling treatment decreased CP contents of indigofera and moringa but not papaya leaves.…”
Section: Chemical Composition and Silage Qualitysupporting
confidence: 86%
“…Indigofera contained higher NDF and ADF than those of papaya and moringa. The NDF and ADF contents of indigofera ranged around 27-31 and 25-28% DM, respectively (Kumalasari et al, 2017), and the values obtained in this experiment were closely similar. Such higher NDF and ADF contents of indigofera as compared to those of moringa were confirmed by ; the authors reported that moringa leaves contained 21.9 and 11.4% of NDF and ADF, respectively.…”
Section: Chemical Composition and Silage Qualitysupporting
confidence: 78%
“…Variasi nilai gizi dari berbagai spesies Indigofera yang terlihat pada tabel 1 dapat disebabkan oleh berbagai macam faktor. Nilai nutrisi hijauan pakan tergantung pada spesies/varitas, lingkungan (tanah, iklim, penggembalaan), bagian tanaman dan umur tanaman (Nelson & Moser,1994;Pearson & Ison, 1997;Kumalasari et al, 2017). Herdiawan & Krisnan (2014)…”
Section: Kandungan Nutrisi Indigofera Spunclassified
“…The optimal allocation of plant layout has been valued by agricultural producers and researchers [2] . The determination of the layout of traditional agricultural crops is mostly based on expert experience [3,4] or field trials [2][3][4][5][6][7][8][9][10][11] . Although the empirical model of experts is simple and practical, it tends to target certain characteristics of an area such as climate, geography, soil type, and crop planted, and therefore has less general applicability.…”
Section: Introduction mentioning
confidence: 99%